Context base editing for splice correction of IVSI-110 β-thalassemia - Basma Naiisseh; Panayiota L. Papasavva; Nikoletta Y. Papaioannou; Marios Tomazou; Lola Koniali; Xenia Felekis; Constantina G. Constantinou; Maria Sitarou; Soteroula Christou; Marina Kleanthous; Carsten W. Lederer; Petros Patsali (Elsevier, 2024)
β-Thalassemia is brought about by defective β-globin (HBB [hemoglobin subunit β]) formation and, in severe cases, requires regular blood transfusion and iron chelation for survival. Genome editing of hematopoietic stem cells allows correction of underlying mutations as curative therapy. As potentially safer alternatives to double-strand-break-based editors, base editors (BEs) catalyze base transitions for precision editing of DNA target sites, prompting us to reclone and evaluate two recently published adenine BEs (ABEs; SpRY and SpG) with relaxed protospacer adjacent motif requirements for their ability to correct the common HBBIVSI-110(G>A) splice mutation. Nucleofection of ABE components as RNA into patient-derived CD34+ cells achieved up to 90% editing of upstream sequence elements critical for aberrant splicing, allowing full characterization of the on-target base-editing profile of each ABE and the detection of differences in on-target insertions and deletions. In addition, this study identifies opposing effects on splice correction for two neighboring context bases, establishes the frequency distribution of multiple BE editing events in the editing window, and shows high-efficiency functional correction of HBBIVSI-110(G>A) for our ABEs, including at the levels of RNA, protein, and erythroid differentiation.